Occurrence of hospital infection among interned elderly in a university hospital - Boas, PJFV (2004)
Objective Hospital infection is an important cause of morbidity and mortality in the elderly population. The objective of this study was to evaluate the occurrence of hospital infection and risk factors associated with it. Methods This is a prospective study of a sample of 332 elderly people, 60 years and older interned in a university hospital, between September 1999 and February 2000. Sample size was calculated according to the Fisher and Belle formula, with a confidence interval of 0.95%,from a total of 760 elderly patients interned in proportion to the number of patients present in each in-patient unit, in the 1997. Criteria for defining hospital infection were those established by the Center for Diseases and Prevention Control. Odds ratio and logistic regression were utilized for statistical analysis of the data. Results The rate of hospital infection was 23.6%. The prevalent topographies of infection were respiratory infections (27.6%), urinary tract infections (26.4%) and surgical wound infections (23.6%). The period of hospitalization of patients who did have hospital infections was 6.9 days, while those who had hospital infections were hospitalized for 15.9 days (p<0.05). Mortality rate among hospitalized patients was 9.6% and the rate of lethality among patients with hospital infection was 22.9% (p<0.05). Risk factors found for hospital infection were cholangiography (odds ratio (OR) =46.4, confidence interval 95% (CI95%) =4.4-485); diabetes mellitus (OR=9.9, CI 95% -4.4-22.3); chronic obstructive pulmonary disease (OR=8.3, CI 95% =2.9-23.7); urinary catheters (OR=5, CI 95% =2.7-11.8); hospitalization with community infection (OR=3.9, CI 95% =1.7-8.9) and mechanic ventilation (OR=3.8, CI 95% =1.9-6.3). Conclusions Hospital infection presented elevated incidence and lethality and it increased the period of hospitalization among the elderly studied.